A mobilidade do consumo no Aglomerado Urbano de Maringá-PR / The mobility of consumption at the Urban Area of Maringá-PR. - Ghizzo, Marcio Roberto; Rocha, Marcio Mendes (Caderno de Geografia, 2016)
No intuito de atender às novas demandas capitalistas que lhes são constantemente instigadas, os homens têm se submetido às imposições deste sistema econômico e realizado um consumo exacerbado. Porém, como a disseminação de bens e serviços não é espacialmente homogênea, o consumidor muitas vezes precisa se submeter à mobilidade para ter acesso a determinadas mercadorias oferecidas nos maiores centros. Este fluxo populacional que se instaura na relação entre cidades é denominado mobilidade do consumo. Privilegiamos, neste artigo, o movimento que converge na cidade de Maringá-PR, procedente das cidades que compõem seu aglomerado urbano, localizada na região Norte Central Paranaense. A mobilidade do consumo acontece em volume significativo e desencadeia uma produção espacial desigual. Palavras–chave: Mobilidade do consumo, Aglomerado urbano de Maringá, Maringá, consumidores. Abstract In the purpose to attend the new capitalists’ demands that are constantly instigated, people have submitted to the impositions from this economic system and achieved an exacerbated consumption. However, as the spreading of property and services aren´t spatially homogeneous, the consumer many times needs to submit himself/herself to the mobility to have access to specific merchandises offered in the biggest centers. This populational flux, which establishes itself in the relationship among the cities, it is denominated Mobility of Consumption. We privileged in this article the movement, which converges in Maringá city, in the state of Paraná, resulting from the cities, which compose its urban area, localized in Paranaense Central North Region. The Mobility of Consumption occurs in meaningful volume and unleashes an uneven spatial production. Keywords: Mobility of Consumption, urban area of Maringá, Maringá, consumers.